Macroscopic Foam‐Like Holey Ultrathin g‐C3N4 Nanosheets for Drastic Improvement of Visible‐Light Photocatalytic Activity. Issue 24 (2nd September 2016) - Li, Yunfeng; Jin, Renxi; Xing, Yan; Li, Junqi; Song, Shuyan; Liu, Xianchun; Li, Mei; Jin, Rongchao
Abstract : Holey ultrathin g‐C3 N4 nanosheets (CNHS) with abundant micro‐, meso‐, and macropores are fabricated by thermal "etching" of bulk g‐C3 N4 . The prepared CNHS possess a unique ultralight characteristic, high specific surface area, more catalytic active sites, and enhanced electron transport ability, leading to a much superior activity in hydrogen generation and photodegradation of pollutant.